PENGARUH PENINGKATAN FLOW RATE GAS METAN TERHADAP SIFAT OPTIS LAPISAN TIPIS AMORF SILIKON KARBON (a-SiC:H) HASIL DEPOSISI METODE DC SPUTTERING - Munisa, Lusitra; Saleh, Rosari (Makara Journal of Science, 2002)
Methane Flow Rate Effects On The Optical Properties of Amorphous Silicon Carbon (a-SiC:H) Films Deposited By DC Sputtering Methods. We have investigated the refractive index (n) and the optical absorption coeffi cient (α) from refl ection and transmission measurements on hydrogenated amorphous silicon carbon (a-SiC:H) fi lms. The a-SiC:H fi lms were prepared by dc sputtering method using silicon target in argon and methane gas mixtures. The refractive index (n) decreases as the methane fl ow rate increase. The optical absorption coeffi cient (α) shifts to higher energy with increasing methane fl ow rate. At higher methane fl ow rate, the fi lms tend to be more disorder and have wider optical gap. The relation of the optical properties and the disorder amorphous network with the compositional properties will be discussed.